Pembangunan Sistem Informasi Pengelolaan Kerja Praktek di Perguruan Tinggi - Eko Budi Setiawan (Universitas Multimedia Nusantara, 2016)
Implementation Work Practice in Higher Education in a subject that must be done by all students to try to implement the knowledge and skills acquired to society or industry. A large number of students who participated in the Job with limited human resources administration of the College governing its implementation, can cause problems in terms of effectiveness and efficiency of reporting and implementation. With practical work management application is expected to help the parties involved in effecting and improve efficiency in all administrative and reporting processes of practical work process. It also can improve the quality of the presentation of the information provided. Index Terms – Aplikasi, Kerja Praktek, Sistem Informasi, Efektif, Efisien